Enzymes for production of whey protein hydrolysates and other value‑added products - Irazoqui, Jose Matias (2024)
Whey is a byproduct of dairy industries, the aqueous portion which separates from cheese during the coagulation of milk. It represents approximately 85–95% of milk’s volume and retains much of its nutrients, including functional proteins and peptides, lipids, lactose, minerals, and vitamins. Due to its composition, mainly proteins and lactose, it can be considered a raw material for value-added products. Whey-derived products are often used to supplement food, as they have shown several physiological efects on the body. Whey protein hydrolysates are reported to have diferent activities, including anti hypertensive, antioxidant, antithrombotic, opioid, antimicrobial, cytomodulatory, and immuno-modulatory. On the other hand, galactooligosaccharides obtained from lactose can be used as prebiotic for benefcial microorganisms for the human gastrointestinal tract. All these compounds can be obtained through physicochemical, microbial, or enzymatic treatments. Particularly, enzymatic processes have the advantage of being highly selective, more stable than chemical transformations, and less polluting, making that the global enzyme market grow at accelerated rates. The sources and diferent products associ ated with the most used enzymes are particularly highlighted in this review. Moreover, we discuss metagenomics as a tool to identify novel proteolytic enzymes, from both cultivable and uncultivable microorganisms, which are expected to have new interesting activities. Finally enzymes for the transformation of whey sugar are reviewed. In this sense, carbozymes with ß-galactosidase activity are capable of lactose hydrolysis, to obtain free monomers, and transgalactosylation for prebiotics production.